Maintenance of the Results of Stage II Lower Limb Lymphedema Treatment after Normalization of Leg Size - Jose Maria Pereira de Godoy; Henrique Jose Pereira de Godoy; Renata Lopes Pinto; Fernando Nestor Facio; Maria de Fatima Guerreiro Godoy (International Journal of Vascular Medicine)
Objective. The aim of this study was to identify strategies to transfer responsibility of the maintenance of the results of lymphedema treatment to the patient. Methods. Maintenance of the reduction of edema was evaluated in a prospective clinical trial in patients with Stage II leg lymphedema. Twenty-one lymphedematous lower limbs were evaluated in Clínica Godoy in 2014 and 2016. The evaluation was done by volumetry at baseline and weekly thereafter for volume control. Patients wore Venosan® cotton 20/30 and 30/40 mmHg elastic compression stockings followed by a custom-made inelastic stocking made of grosgrain fabric. The Friedman test for multiple comparisons and Conover post hoc test were used for statistical analysis with an alpha error of 5%. Results. On comparing leg volume changes using the different types of stockings, the 20/30 mmHg elastic compression stockings failed in the first week to maintain the volume reductions but the 30/40 mmHg compression stockings did not allow significant increases in volume (p value > 0.05). During one week, the grosgrain stocking reduced leg volumes to baseline values (p value = 0.24). Conclusion. Higher compression of elastic stockings is better than lower compression but the inelastic grosgrain stocking is even better than both to maintain the results.